Design and Build Microstrip AntennasMultiple Input Multiple Output (MIMO) Wideband Elements For WIFI Access-point Applications - Muthia Haifa; Aprinal Adila A; Popy Maria (International Journal of Wireless And Multimedia Communications, 2024)
Technology in the field of telecommunications continues to experience development. One of them is the Multiple Input Multiple Output (MIMO) antenna used in WIFI access point applications using the MIMO technique to increase the need for large amounts of data transfer. In  designing and  manufacturing MIMO antennas for WIFI access point applications with a size of 110 mm x 112 mm using FR-4 substrate specifications with a thickness of 1.6 mm. The antenna consists of four ports and in each corner of the groundplane there are four slots to achieve good isolation and produce good bandwidth. The antenna simulation produces a bandwidth of 1.0516 GHz with a frequency of 2.4 GHz, return loss -12.78 dB, isolation -16.08 dB, and VSWR 1.53 dB. Meanwhile, fabricated antennas produce bandwidth of more than 100 MHz with a frequency of 2.4 GHz, return loss -13.5 dB, isolation -18.8 dB, and VSWR 1.29 dB. Antenna simulation using the CST Studio Suite 2019 software application